Antibacterial Activity of Soursop (Annona muricata L.) Leaf and Fruit Extracts Against Streptococcus mutans - Putri, Diva Azzahra Rizqika; Zuraidah, Zuraidah; Amin, Nurdin (Universitas Sultan Ageng Tirtayasa, 2025)
Dental caries is a common oral health problem, with Streptococcus mutans playing a key role. This bacterium metabolizes sucrose into lactic acid, leading to tooth enamel demineralization and cavities. Soursop (Annona muricata L.) plants, known for their antibacterial bioactive compounds, are often used traditionally to treat microbial infections. This study investigated the inhibitory effects of soursop leaf and fruit extracts on Streptococcus mutans growth using a completely randomized experimental design and the Kirby-Bauer disc diffusion method. Results showed that leaf and fruit extracts at 100% concentration exhibited the strongest inhibition (14.86 mm and 14.83 mm, respectively). The weakest inhibition was observed at 40% concentration (10.60 mm for leaf and 10.13 mm for fruit extracts). However, the average inhibition diameters for both soursop extracts were smaller than the positive control’s average of 27.80 mm. Based on these findings, it can be concluded that Soursop leaf and fruit extracts (Annona muricata L.) possess antibacterial activity against Streptococcus mutans.